Investigation of University Students’ Engagement and Its Relationship to Burnout, Personality Traits and Academic Achievement - Mor Di̇rli̇k, Ezgi; Külekçi̇, Erkan; Akcaoğlu, Mustafa Öztürk (Afyon Kocatepe University, 2022)
In the field of education, researchers have been studying individuals’ psychological constructs such as burn-out, engagement and personality traits to better understand their commitment. To this end, we examined the relationship among school engagement and burnout, personality traits and academic achievement in a sample of university students (N = 301). The data were collected through Maslach Burnout Inventory-Student Survey, Utrecht Work Engagement Scale-Students Form and The Quick Big Five Personality Test. In order to test the hypotheses of the study descriptive statistics, zero-order correlations, regression analyses were performed. Results indicated that the relationships among the dimensions of burnout and school engagement were the strongest. On the other hand, only conscientiousness had a positive medium level of correlation with school engagement among the assessed personality traits. We also found out that school engagement could be predicted by efficacy, exhaustion, cynicism, conscientiousness and emotional stability scores. The findings offered valuable insights to enhance our understanding of the relationships between school engagement and personality traits and burnout. Eğitim alanında, öğretme ve öğrenme sürecini daha iyi anlamak için araştırmacılar bireylerin tükenmişlik, bağlılık ve kişilik türleri gibi psikolojik özelliklerini incelenmektedir. Bu çalışmada, üniversite öğrencilerinin (N = 301) okul bağlılığı ile tükenmişlik, kişilik özellikleri ve akademik başarı arasındaki ilişki incelenmiştir. Araştırma verileri Maslach Tükenmişlik Envanteri-Öğrenci Formu, Utrecht İşe Bağlılık Ölçeği-Öğrenci Formu ve Hızlı Büyük Beşli Kişilik Testi ile toplanmıştır. Araştırmanın hipotezlerini test etmek için betimsel istatistikler, basit korelasyon ve regresyon analizleri yapılmıştır. Araştırma bulguları, en güçlü ilişkinin tükenmişlik ve okul bağlılığı boyutları arasında olduğunu göstermiştir. Öte yandan, değerlendirilen kişilik özellikleri arasında sadece sorumluluk ile okula bağlılık arasında pozitif orta düzeyde bir ilişki bulunmuştur. Ayrıca okul bağlılığının yeterlik, tükenmişlik, duyarsızlaşma, sorumluluk ve duygusal denge puanları ile yordanabileceği bulunmuştur. Araştırma okul bağlılığı ile kişilik özellikleri ve tükenmişlik arasındaki ilişkilere dair öğretme ve öğrenme sürecine katkı sağlayacak bulgular tartışılmıştır.
Keywords: Personality Traits; Alan Eğitimleri; Academic Achievement; Okula Bağlılık; Other Fields of Education; academic achievement; burnout; personality traits; school engagement; akademik başarı; kişilik özellikleri; okula bağlılık; tükenmişlik; Akademik Başarı; Burnout; School Engagement; Kişilik Özellikleri; Tükenmişlik; 4. Education